Ketenangan Hati Persepektif Al-Qur’an: Analisis Tafsir Maudhu’i Dalam Surah Ar-Rad Ayat 28 - Fauziah Nur Ariza; Rahma Rizki Nasution; Rahmah Aulia Saragih; Hotman Isad Siregar; Nurhalizah; Sabrina Bila Putri; Itcat Martua Harahap; Hafiz Purba (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
Peace of mind is often discussed in the Qur'an but is still not explicit. This study of the concept of peace of mind in the Qur'an Maudhu'i Tafsir approach to the Ar-Rad verse 28, and the theology of dhikr and Al-Qulub. Through analysis of classical and contemporary sources of interpretation, that the peace referred to in the verse is not only from one side but a spiritual state in the awareness of monotheism. This study contributes to the study of the interpretation of the Qur'an by discussing peace of mind is not merely advice but the understanding of monotheism and existence for human psychology and spirituality. Thus, this study positions La Ilaha Illa Allah not only as theology, but as a Qur'anic paradigm for steadfastness